Evapotranspiration is the only relevant source of moisture at the onset of the rainy season in South America - Versieux, Verônica Karoliny Nunes Caetano Pereira (Universidade Federal de Viçosa, 2024)
The South American Monsoon System, which transports moisture from Amazonia to Central-West Brazil, is an important moisture source for the summer rainy season in this region. While local evapotranspiration also contributes to the atmospheric moisture supply, the balance between local and remote sources during the onset of the rainy season remains uncertain. This research aimed to quantify the role of local evapotranspiration in initiating the rainy season in Central-West Brazil. By utilizing data from various sources, such as remote sensing (MODIS), modern reanalysis (ECMWF’s ERA5), and composite products of rainfall (CHIRPS), and analyzing them in a comparative way, we conclusively found that local evapotranspiration is the only relevant source of moisture to the atmosphere during the dry-to-wet season transition, preceding the establishment of the monsoon system. Keywords: evapotranspiration; monsoon onset; MODIS; ERA5; CHIRPS

O Sistema de Monções da América do Sul transporta a umidade da Amazônia para o Centro-Oeste do Brasil, tornando-se uma importante fonte de umidade para a estação chuvosa de verão nesta região. Embora a evapotranspiração local também contribua para o suprimento de umidade atmosférica, ele ainda não equilibra as fontes locais e remotas durante o início da estação chuvosa. Essa pesquisa tem o objetivo de quantificar o papel da evapotranspiração local no início da estação chuvosa no Centro-Oeste do Brasil. Utilizando dados de várias fontes, como sensoriamento remoto (MODIS), reanálise moderna (ERA5 do ECMWF) e produtos compostos de precipitação (CHIRPS), e analisando-os de forma comparativa, conclui-se que a evapotranspiração local é a única fonte relevante de umidade para a atmosfera durante a transição da estação seca para a úmida, antes do estabelecimento do Sistema de Monções. Palavras-chave: evapotranspiração; início das monções; MODIS; ERA5; CHIRPS
Evapotranspiração local é a única fonte relevante de umidade no início da estação chuvosa na América do Sul
Keywords: Evapotranspiração; Monções; Precipitação (Meteorologia) - Previsão; Satélites meteorológicos; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::METEOROLOGIA::CLIMATOLOGIA